Diagnosis of traditional Chinese medicine constitution by integrating indices of tongue, acoustic sound, and pulse - Huang, Chun-Jen; Lin, Hung-Jen; Liao, Wen-Ling; Ceurvels, Will; Su, Shan-Yu (European journal of integrative medicine, 2019)
Inspection, auscultation, and pulse-taking are the three physical examinations used by traditional Chinese medicine (TCM) practitioners to diagnose constitution. The aim of this study was to integrate biological signals extracted from these three examinations, including tongue image, waves of acoustic sound, and pulse waveforms, into the same model in order to identify TCM constitutions. Tongue images, acoustic sound, and pulse waveforms were abstracted from 274 subjects, and indices of biological signals were extracted. Constitution scores were measured using the Nine-Constitution Scale questionnaire. Association between indices and constitution scores were analyzed by Pearson correlation analysis. For each of the eight abnormal constitutions, indices significantly correlated to the abnormal constitution were further used as arguments in a linear regression model to build an equation for predicting the constitution score. Tongue indices that were identified to be associated with abnormal constitutions included the G, B, S and b color values, maximum width of tongue body, number of red spots on the tongue surface, and proportion of scalloped tongue margin. Acoustic sound indices included intensity, average number of zero-crossing, high spectral energy ratio, and pitch of the acoustic sound. Pulse waveform indices included the height of the main wave, unsmooth wave, single systolic area, and rapid ejection time. This study identified indices that are associated with scores of abnormal constitutions. Indices having a larger correlation coefficient can be considered to have larger relative weight in determination of the corresponding constitution. The equations make it possible to predict constitution scores based on biological signals of the tongue, acoustic sound, and pulse.